Laser polishing of PBF-LB manufactured stainless steel surfaces - Karlsson J; Väisänen I; Tourunen E; Piironen A; Gopaluni A; Salminen A (United Kingdom, 2025)
Laser powder bed fusion (PBF-LB) is additive manufacturing where material is added layer by layer. This technology has revolutionized the manufacturing during last few recent years by enabling more efficient material usage and more functions to each component. However, for many industrial cases, the PBF-LB surfaces need an additional finishing operation like the machining or polishing operation. Laser polishing process was studied to solve the problems of traditional technologies to improve the surface quality and to enable automation of it. In this study parts were manufactured by PBF-LB of austenitic stainless steel (AISI 316L) into shapes of mechanical property testing samples in different orientations and locations in building platform. The surface roughness was measured prior and after polishing. The experiments showed that considerable surface smoothening even up to 85% (Sa from 48 μm to 11 μm) was reached in two treatments.
NOLAMP- Nordic Laser Materials Processing Conference (19TH-NOLAMP-2023) 22/08/2023 - 24/08/2023 Turku, Finland